Business Opportunity Human Resource Information System for a Human Resource Department to Create Career Path and Performance Evaluation - Ni Nyoman Sawitri; Primadi Candra Susanto; Sugeng Suroso; Sarinah Sihombing (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of the study is to describe and show the role of HRIS related to its use, business opportunities, and employee performance evaluation, which is used from existing scientific articles and then given a perspective by researchers in this scientific article. Research methods used. Qualitative research with a literary research approach. This method uses the keywords HRIS, Human Capital and Career to summarize articles from Google Scholar, Research Gate and other reputable international journals. Literature titles, abstracts and keywords are used to filter the criteria of the filtered literature again, reading the entire content. The  results of research with research variables are related to  research (Nagendra &; Deshpande, 2014), (Irum &; Yadav, 2019), (Widhianto, 2002), (Jonni &; Husein, 2019), and there are also research results that conflict with manual use with HRIS from research results  (Edhy Permata, 2019), the last research from (Susanto &; Parmenas, 2021) where business and development opportunities for companies to use HRIS in MSMEs. Variables that can be used for further research HRIS Skills Inventory, HRIS Training Needs Analysis, HRIS Succession Planning and HRIS Workforce Needs and Supply Analysis, workforce planning, HR business needs and decision making, cheap and easy information technology from the business side, employee training, employee violation information, employee payroll, business   acquisition records , HRIS is still followed by manual processes, business opportunities and development of system usage